Cervical spine instability and canal stenosis caused by rheumatoid arthritis - Eko Agus Subagio; Seok Woo Kim (Indoscholar, 2020)
Rheumatoid arthritis (RA) is an inflammatory autoimmune disease that impacts on weakening ligaments, synovial arthritis and cartilage damage. The effect that can occur is instability and neural compression in the upper and sub-axial cervical. The prevalence of atlantoaxial instability (AAI) is around 40-80% among rheumatoid patients, but it is interesting to examine the clinical symptoms that are not so visible despite radiological instability confirmed on the cervical spine. However, once the clinical symptoms of myelopathy occur, the mortality rate will increase sharply. We report a case of a 66-years old female who was admitted to our hospital with gait disturbance and weakness of her lower extremities. Radiographic evaluation of the cervical spine showed erosive destruction of the odontoid process of C2, anterior atlantoaxial subluxation, and thickened yellow ligaments from C3 to C7. Surgery was performed by removal of the posterior arch of C1 and laminectomy C3 to C7, posterior occipito-cervical screw fixation from C3 to C7, combined with atlantoaxial transpedicular screw fixation. A sterno sub-occipitomandibular immobilization (SOMI) orthosis was applied for postoperative immobilization for 12 weeks. Improvement of motoric status noted after surgery.